2011
DOI: 10.1007/s12274-011-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

Size-tunable nanoparticles composed of dextran-b-poly(D,L-lactide) for drug delivery applications

Abstract: Nanoparticles (NPs) formulated using self-assembly of block copolymers have attracted significant attention as nano-scaled drug delivery vehicles. Here we report the development of a biodegradable NP using self-assembly of a linear amphiphilic block copolymer, Dex-b-PLA, composed of poly(D,L-lactide), and dextran. The size of the NPs can be precisely tuned between 15 and 70 nm by altering the molecular weight (M W ) of the two polymer chains. Using doxorubicin as a model drug, we demonstrated that the NPs can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 53 publications
0
53
0
1
Order By: Relevance
“…1(a)). Since a diameter of more than 7 nm was previously reported to be able to escape renal filtration and urinary excretion, this suggests that the devised micelle may potentially exhibit a prolonged circulatory half-life and enhance the accumulation of particles at the tumor site in vivo through the EPR effect [46,47]. Using FETEM, we observed that the micelles were spherical in shape and had a smooth surface ( Fig.…”
Section: Characterization Of Hybrid Micellesmentioning
confidence: 74%
“…1(a)). Since a diameter of more than 7 nm was previously reported to be able to escape renal filtration and urinary excretion, this suggests that the devised micelle may potentially exhibit a prolonged circulatory half-life and enhance the accumulation of particles at the tumor site in vivo through the EPR effect [46,47]. Using FETEM, we observed that the micelles were spherical in shape and had a smooth surface ( Fig.…”
Section: Characterization Of Hybrid Micellesmentioning
confidence: 74%
“…Four samples were prepared by mixing (1) 0.5 mL of a 2.5 mg/mL solution of doxorubicin hydrochloride with 0.5 mL of PBS (drug-only control, to correct for membrane effects on release kinetics); (2) 0.5 mL of a 60 wt% C18-PVP-55kDa solution in PBS with 0.5 mL of a 2.5 mg/mL doxorubicin hydrochloride solution in PBS (to assess the effect of the associative hydrogel on release kinetics); (3) 0.5 mL of a 650 mg/mL suspension of drug-loaded nanoparticles in PBS with 0.5 mL of PBS (to assess the release kinetics achieved with nanoparticles alone); and (4) 0.5 mL of a 650 mg/mL suspension of drug-loaded nanoparticles in PBS with 0.5 mL of a 60 wt% C18-PVP-55kDa solution in PBS (to assess the combined effect of nanoparticles and the associative hydrogel on release kinetics). For nanoparticle formulations, nanoparticles based on the self-assembly of dextran-blockpoly(lactide-co-glycolic acid) (dex-b-PLGA) were produced as previously described (Verma et al, 2012), dried in vacuo, and then rehydrated at a concentration of 50 mg/mL in a solution of 50 mg/ mL doxorubicin hydrochloride in water. These solutions were sonicated for 10 min in a bath sonicator to allow the drugs to diffuse into the nanoparticles and then left stirring for three days to ensure equilibrium had been attained.…”
Section: Drug Release Kineticsmentioning
confidence: 99%
“…Nanoparticles are typically used in drug delivery applications because of high drug encapsulation efficiency [35], controlled drug release and incorporation of diagnostic agents [36,37]. One of the major challenges with drug delivery is achieving specificity with cellular uptake.…”
Section: Microparticles and Nanoparticlesmentioning
confidence: 99%
“…The amount of lysis was compared to a negative control of veronal buffered saline and positive control of deionized water. Curdlan-graft-PEG nanoparticles showed hemolysis below 5% at clinically relevant concentrations [5], which is considered biocompatible [35]. Therefore, nanoparticles and microparticles based on 1,3--glucans provide promising opportunities for drug delivery as structural units and as targeting ligands.…”
Section: Microparticles and Nanoparticlesmentioning
confidence: 99%